Effects of intermittent hypoxia on heart rate variability during rest and exercise - Povea, C.; Schmitt, L.; Brugniaux, J.; Nicolet, G.; Richalet, J. P.; Fouillot, J. P. (High Altitude Medicine & Biology, 2005)
Changes in heart rate variability induced by an intermittent exposure to hypoxia were evaluated in athletes unacclimatized to altitude. Twenty national elite athletes trained for 13 days at 1200 m and either lived and slept at 1200 m (live low, train low, LLTL) or between 2500 and 3000 m (live high, train low, LHTL). Subjects were investigated at 1200 m prior to and at the end of the 13-day training camp. Exposure to acute hypoxia (11.5% O2) during exercise resulted in a significant decrease in spectral components of heart rate variability in comparison with exercise in normoxia: total power (p < 0.001), low-frequency component. LF (p < 0.001), high-frequency component, HF (p < 0.05). Following acclimatization, the LHTL group increased its LF component (p < 0.01) and LF/HF ratio during exercise in hypoxia after the training period. In parallel, exposure to intermittent hypoxia caused an increased ventilatory response to hypoxia. Acclimatization modified the correlation between the ventilatory response to hypoxia at rest and the difference in total power between normoxia and hypoxia (r 2 = 0.65, p < 0.001). The increase in total power, LF component, and LF/HF ratio suggests that intermittent hypoxic training increased the response of the autonomic nervous system mainly through increased sympathetic activity.